PENGARUH KEMISKINAN TERHADAP AKSES LAYANAN KESEHATAN DI KABUPATEN MIMIKA - Borgen Extri Arens Lona; Herniagus Tandi Dannari, Abu Bakar (CV. ADIBA AISHA AMIRA, 2024)
This study aims to determine the effect of poverty on access to healthcare services in Mimika Regency. The data collection technique used to gather data in this research was a questionnaire, and the application used for data analysis was SPSS version 25. The data analysis in this study employed Chi-square analysis. Based on the data analysis results, the author concludes that poverty does have an impact on access to healthcare services in Mimika Regency. Four indicators of healthcare access were assessed in the study—distance, transportation costs, friendliness, and satisfaction—all of which showed a significant influence of poverty on healthcare access